การเปรียบเทียบระหว่างประสิทธิภาพต้นทุน และประสิทธิภาพกำไร โดยใช้วิธีการกระจายแบบอิสระ : กรณีศึกษาธนาคารในประเทศไทย - ภณิดา ภิญโญศรี (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The purpose of this research is to study and compare the cost and profit efficiency of banks in Thailand. A Distribution Free Approach (DFA) based on translog function form, Fourier function forn, and linear Spin function form will be employed to generate cost efficiency, standard profit efficiency, and alternative profit efficiency. In Distribution Free Approach, thsi study uses pooled OLS regression model to estimate cost function, standard profit function, and alternative profit function. The data used in this paper covers the data of Thai banks operating during the period between 2006 and 2009. The result shows that cost efficiency scores of Thai banks are between 0.02 and 1.00. The standard profit efficiency scores of Thai banks are between 0.0444 and 1.00. The alternative profit efficiency scores of Thai banks are between 0.0069 and 1.00. In addition, this study also reveals that Fourier function is the most appropriate functional form to estimate cost and profit efficiency of banks in Thailand. It is more appropriate thatn translog functional from amd the Linear Spin functional form amd R2 of cost efficiency model, standard profit efficiency model, and alternative profit efficiency model are 0.935, 0.907 and 0.908, respectively